Susceptibility profile of Salmonella against the antibacterial activity of propolis produced in two regions of Brazil - R. O. Orsi; J. M. Sforcin; V. L. M. Rall; S. R. C. Funari; Luciano Barbosa; JR A. Fernandes (Journal of Venomous Animals and Toxins including Tropical Diseases, 2005)
Propolis antibiotic action has been widely investigated. This assay was carried out in order to observe the in vitro antibacterial activity of propolis against Salmonella enteritidis isolated from food and Salmonella typhimurium isolated from human infections. Propolis was collected by Apis mellifera in two regions of Brazil (Mossoró, Rio Grande do Norte State; and Urubici, Santa Catarina State). Both strains survival percentage decreased with time of incubation in Ethanolic Extracts of Propolis (EEP), demonstrating bactericidal effect after 24 hours. It was also observed that EEP from Mossoró was more effective than that from Urubici. The control of the propolis solvent - 70% ethanol - was less effective than EEP, showing only a bacteriostatic effect. We can conclude that propolis shows an activity against Gram-negative bacteria that varies according to the geographical region where it was collected by bees.